2021
DOI: 10.3390/cells10071708
|View full text |Cite
|
Sign up to set email alerts
|

Human Tissue Angiotensin Converting Enzyme (ACE) Activity Is Regulated by Genetic Polymorphisms, Posttranslational Modifications, Endogenous Inhibitors and Secretion in the Serum, Lungs and Heart

Abstract: Objective: Inhibitors of the angiotensin converting enzyme (ACE) are the primarily chosen drugs to treat heart failure and hypertension. Moreover, an imbalance in tissue ACE/ACE2 activity is implicated in COVID-19. In the present study, we tested the relationships between circulating and tissue (lung and heart) ACE levels in men. Methods: Serum, lung (n = 91) and heart (n = 72) tissue samples were collected from Caucasian patients undergoing lung surgery or heart transplantation. ACE I/D genotype, ACE concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Perhaps the normal age-related protective response (posited above) may become dysfunctional in AD, for instance in the presence of Aβ peptides. Alternatively, disease-associated post-translational modification, altered secretion, or changes in the concentrations of potential endogenous inhibitors of ACE-1, may account for disparities between ACE-1 protein and activity in AD ( 38 ). We did not observe disease-associated changes to ACE-2 activity in this study compared to our previous study ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the normal age-related protective response (posited above) may become dysfunctional in AD, for instance in the presence of Aβ peptides. Alternatively, disease-associated post-translational modification, altered secretion, or changes in the concentrations of potential endogenous inhibitors of ACE-1, may account for disparities between ACE-1 protein and activity in AD ( 38 ). We did not observe disease-associated changes to ACE-2 activity in this study compared to our previous study ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…The collection of human samples was approved by the Ethics Committee of the University of Debrecen (Hungary) as described in detail previously [ 27 ]. All corresponding procedures were carried out in accordance with institutional guidelines and the Code of Ethics of the World Medical Association (Declaration of Helsinki).…”
Section: Methodsmentioning
confidence: 99%
“…However, some studies failed to discern any relationship between the ACE gene polymorphism and CAD in patients with diabetes [ 35 , 36 ]. A possible mechanism suggests that the ACE DD genotype is involved in increasing the vasoconstrictor angiotensin II as well as the degradation of the vasodilator bradykinin, which increases resistance to insulin [ 37 ]. Our results are consistent with data obtained from different studies [ 38 , 39 , 40 ]; we found that the ACE (rs4646994) D allele increases the risk of CAD in T2DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that a gene–environment interaction may play a significant role in the predisposition to CAD [ 35 , 36 ]. The insertion/deletion (I/D) (rs4646994) polymorphism in intron 16 of the ACE gene is considered an important genetic determinant of CAD and hypertension [ 37 , 42 ]. There is controversy related to the role of the ACE D/I polymorphism in the risk of CAD and myocardial infarction (MI) [ 43 ].…”
Section: Discussionmentioning
confidence: 99%